Electronic communication data, jurisdiction and international legal cooperation: Brazil and United States - Ana Paula Gonzatti da Silva (Revista Brasileira de Direito Processual Penal)
This study aims to find out if it is necessary to resort to international legal cooperation mechanisms to obtain data which are under control internet application providers established abroad. Therefore, initially, draws up a brief overview of international legal cooperation (about what and why we spoken). After, seeks to know what the parameters are for that particular entity is determined under national jurisdiction, in order to determine whether or not it is necessary to activate the mechanisms of international legal cooperation. Next, more specifically, aspects of the mutual legal assistance treaty between Brazil and the United States and the specificities in the American legislation regarding the protection of disclosure of data are discussed.In the face of this scenario, critical considerations are made if international legal cooperation procedures are not followed.Finally, it seeks to bring proposals so that the norms of international law, especially sovereignty, are respected.